New Technological Demands: The Methodological Framework for an INIAs/BID/ISNAR Project - International Service for National Agricultural Research (International Service for National Agricultural Research, 1998)
This book presents the conceptual and methodological basis for the cooperative research project titled "Identifying and Responding to New Technological Demands for Agricultural Research from Agroindustry and Natural Resource Management", that was jointly executed by several Latin American national agricultural research institutes (Argentina; South America; , Brazil, Chile, Colombia, Mexico, and Venezuela), assisted by the regional coordinating programs PROCISUR and PROCIANDINO, as well as ISNAR. The document first analyzes the socioeconomic trends in Latin America and the likely effects of these on the agricultural sector and the technological development of the continent. It then determines the consequences for the various facets of agricultural research including traditional production research, natural resource management research, agroindustrial research.The second part describes the development of the project's methodological framework. The third section presents outlines of the six case studies that were designed for the project. Three of these examined the strategic, programmatic, and operational aspects of natural resource concerns; the three others examined those aspects dealt of the agroindustrial sector.